Additive Manufacturing of Multi-material Polymer Parts Within the Collaborative Research Center 814 - Setter, Robert; Stichel, Thomas; Schuffenhauer, Thomas; Kopp, Sebastian-Paul; Roth, Stephan; Wudy, Katrin (Lecture Notes in Mechanical Engineering, 2021)
During the past years additive manufacturing (AM) has revolutionized the manufacturing world by enabling rapid generation of geometrically-intricate designs. However, up to now in laser and beam-based AM of polymers only single powder materials whether filled or pure plastics can be processed. One aim of the Collaborative Research Center 814 (CRC 814) – Additive Manufacturing is to establish new process technologies to produce multi-material polymer parts in AM. Therefore, two different strategies basing on Laser Sintering (LS) will be explored: On the one side, selective powder deposition technologies like vibrating nozzles or electrophotography are investigated, which enable to lay down different powders beside each other in one process. On the other side, a liquid reactive UV-curing thermoset is implemented into the LS process chamber. After curing of the UV-curing thermoset the powder beside the cured thermoset is molten by the use of the CO2 laser. Both strategies allow the generation of multi-material parts consisting of material regions with different functional properties.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Additive Manufacturing; Binder Jetting; Laser Sintering; Multi-material parts

Bottom-Up Design of Composite Supraparticles for Powder-Based Additive Manufacturing - Canziani, Herbert; Chiera, Salvatore; Schuffenhauer, Thomas; Kopp, Sebastian-Paul; Metzger, Florian; Bück, Andreas; Schmidt, Michael; Vogel, Nicolas (Small, 2020)
Additive manufacturing promises high flexibility and customized product design. Powder bed fusion processes use a laser to melt a polymer powder at predefined locations and iterate the scheme to build 3D objects. The design of flowable powders is a critical parameter for a successful fabrication process that currently limits the choice of available materials. Here, a bottom-up process is introduced to fabricate tailored polymer- and composite supraparticles for powder-based additive manufacturing processes by controlled aggregation of colloidal primary particles. These supraparticles exhibit a near-spherical shape and tailored composition, morphology, and surface roughness. These parameters can be precisely controlled by the mixing and size ratio of the primary particles. Polystyrene/silica composite particles are chosen as a model system to establish structure–property relations connecting shape, morphology, and surface roughness to the adhesion within the powder, which is accessed by tensile strength measurements. The adhesive properties are then connected to powder flowability and it is shown that the resulting powders allow the formation of dense powder films with uniform coverage. Finally, successful powder bed fusion is demonstrated by producing macroscopic single layer specimens with uniform distribution of nanoscale silica additives.
CRIS-Team Scopus Importer:2020-07-10
Keywords: additive manufacturing; composite powders; nanoscale; spray drying; supraparticles

Employment of an Extended Double-Integrating-Sphere System to Investigate Thermo-optical Material Properties for Powder Bed Fusion - Schuffenhauer, Thomas; Stichel, Thomas; Schmidt, Michael (Journal of Materials Engineering and Performance, 2021)
The optical energy input during laser-based powder bed fusion of polymers (PBF-LB/P) is influenced by a variety of process parameters (e.g., energy density) and powder material properties (e.g. optical properties, additives). Qualification of newly developed and/or modified powder materials still requires extensive, empirical parameter studies to assess processibility and find suitable process strategies. For powder characterization, a double-integrating-sphere system with an intervening hot stage, which allows accurate sample heating during the measurement of the optical properties, is presented and described. For qualification of the system and the associated characterization method for the PBF-LB/P process, the interaction of a collimated CO2 laser beam with selected polyamide powder materials during heating and cooling is investigated. The obtained results illustrate the suitability of the presented thermo-optical characterization technique, i.e., the temperature-dependent measurement of radiation reflected by and transmitted through the samples, for the systematical investigation of material-related (i.e., additives) and process-related (i.e., preheating temperature, layer height) influences on the beam-matter interaction.
CRIS-Team Scopus Importer:2021-03-19
Keywords: integrating sphere; material characterization; optical properties; polymer; powder bed fusion

Experimental determination of scattering processes in the interaction of laser radiation with polyamide 12 powder - Schuffenhauer, Thomas; Stichel, Thomas; Schmidt, Michael (Procedia CIRP, 2020)
Energy density, scanning strategy and laser spot size are some of the parameters influencing the optical energy input during laser-based powder bed fusion of polymers. For newly developed polymer powders, such parameters must still be determined empirically. Understanding the complex mechanisms underlying the beam-matter interaction, including absorption characteristics or multiple scattering behavior, is crucial to predict material processability and to improve interlayer fusion for enhanced final part properties. A measurement system based on two integrating spheres is employed to analyze the scattering processes during the interaction of a CO2 laser beam with polymeric powder materials. The setup is used to measure total reflection from the sample surface as well as unscattered and diffuse transmission through the sample. The resulting optical properties of polyamide 12 powder are evaluated and compared to those of thin films of the same base material. Thus, the influence of particle interfaces on the energy deposition characteristics can be analyzed qualitatively.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Integrating spheres; Laser sintering; Optical properties; Polyamide 12; Polymers; Powder bed fusion

How colloidal surface additivation of polyamide 12 powders with well-dispersed silver nanoparticles influences the crystallization already at low 0.01 vol% - Hupfeld, Tim; Sommereyns, Alexander; Schuffenhauer, Thomas; Zhuravlev, Evgeny; Krebs, Moritz; Gann, Stan; Keßler, Olaf; Schmidt, Michael; Gökce, Bilal; Barcikowski, Stephan (Additive Manufacturing, 2020)
As Additive Manufacturing (AM) is fast-growing, properties adaption of feedstock materials for AM is becoming more and more relevant due to high quality standards in industrial applications. Compared to traditional manufacturing techniques like injection molding, laser powder bed fusion (PBF-LB) of polymers has a very limited variety of processable materials, which is a major obstacle for future growth. Nanocomposites are an established material class for addressing the limitations in PBF-LB but often show poor dispersion of the nanomaterial in/on the polymer powder. Especially in the context of plasmonic nanomaterials and composites, where the state of aggregation considerably influences the optical properties, dispersion plays an important role. Our study presents a deeper understanding of the colloidal surface additivation of polyamide 12 (PA12) powders with laser-generated plasmonic silver nanoparticles, leading to high dispersion of the nanoparticles on the micropowder surface with good reproducibility. The additivation is ruled by colloidal stability and control of electrostatic forces between particles and resulted in powders that could successfully be processed on a PBF-LB machine to generate plasmonic-functionalized parts. Finally, we introduce the surface specific nanoparticle dose (surf%) as scaling key parameter complementary to the commonly used mass specific dose (wt%) to appropriately describe nanoparticle load, proving the effect of such surface additivation on the recrystallization behavior of PA12. Via flash calorimetry, already at 0.01 vol% silver load, significant nanoparticle-induced heterogeneous nucleation effects are evident, whereas the thermal properties analyzed by conventional calorimetry remain unaffected.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Electrostatic deposition; Fast scanning calorimetry (FSC); Laser ablation in liquid (LAL); Laser powder bed fusion (PBF-LB); Nanocomposite; Selective laser sintering (SLS); Surface functionalization